2017
DOI: 10.1038/s41598-017-15161-7
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral changes after nicotine challenge are associated with α7 nicotinic acetylcholine receptor-stimulated glutamate release in the rat dorsal striatum

Abstract: Neurochemical alterations associated with behavioral responses induced by re-exposure to nicotine have not been sufficiently characterized in the dorsal striatum. Herein, we report on changes in glutamate concentrations in the rat dorsal striatum associated with behavioral alterations after nicotine challenge. Nicotine challenge (0.4 mg/kg/day, subcutaneous) significantly increased extracellular glutamate concentrations up to the level observed with repeated nicotine administration. This increase occurred in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 55 publications
1
52
0
Order By: Relevance
“…The present study indicated that co-exposure of EtOH and NIC increased mGlurR1 expression in the NAc. Studies have found that phasic exposure to EtOH or NIC resulted in a marked increase in the total extracellular concentrations of glutamate, which might indicate increased firing of medium spiny neurons (Griffin III et al, 2014, Griffin et al, 2015, Ryu et al, 2017. We suggest here that this A C C E P T E D M A N U S C R I P T 20 effect might increase the expression of post-synaptic glutamate receptors such as mGluR1 as a compensatory mechanism.…”
Section: Accepted Manuscript 19mentioning
confidence: 61%
“…The present study indicated that co-exposure of EtOH and NIC increased mGlurR1 expression in the NAc. Studies have found that phasic exposure to EtOH or NIC resulted in a marked increase in the total extracellular concentrations of glutamate, which might indicate increased firing of medium spiny neurons (Griffin III et al, 2014, Griffin et al, 2015, Ryu et al, 2017. We suggest here that this A C C E P T E D M A N U S C R I P T 20 effect might increase the expression of post-synaptic glutamate receptors such as mGluR1 as a compensatory mechanism.…”
Section: Accepted Manuscript 19mentioning
confidence: 61%
“…The two major subtypes of CNS nicotinic receptors, α7 and α4β2 are expressed on cell bodies and synaptic terminals (Wonnacot, ; Parikh et al , ; Puddifoot et al ; Howe et al ) where they promote the influx of extracellular calcium leading to the release of neurotransmitters (Turner ; Zappettini et al , ). Nicotinic receptors can regulate the release of, at least, glutamate (McGehee et al, ; Gray et al, ; Albuquerque et al ; Gu et al, ; Puddifoot et al ; Pistillo et al , ; Howe et al ; Ryu et al ) and can modulate the release of GABA (Gray et al, ; Le Magueresse et al, ), dopamine (Schilstrom et al, ,b; Kaiser and Wonnacott ; Livingstone and Wonnacott, ; Livingstone et al ) and norepinephrine (Pittaluga and Raiteri ; Pittaluga et al ; Raiteri et al ; Li et al, ). It is reasonable to expect that the release of many other transmitters and modulators including serotonin, glycine, neuroactive peptides and perhaps kynurenines, proteases, cytokines and other factors may also be affected by nicotinic receptors on glia or synaptic terminals or cell bodies.…”
Section: Interpreting Resultsmentioning
confidence: 99%
“…The dose used for subcutaneous (s.c.) nicotine (0.4 mg/kg/day) administration was determined from previous studies (Matta et al, 2007 ; Ryu et al, 2017 ). The extracted CSC was dissolved in 1% DMSO/0.9% NaCl and diluted to make working solutions with a nicotine content of 0.4 mg, and were then adjusted to pH 7.2–7.4 with NaOH.…”
Section: Methodsmentioning
confidence: 99%
“…For example, repeated exposure to nicotine increases glutamate release in the NAc, VTA and PFC by stimulating nAChRs (Lambe et al, 2003 ; Changeux, 2010 ; Shameem and Patel, 2012 ; Falasca et al, 2014 ). Repeated and challenge administrations of nicotine after nicotine abstinence following repeated nicotine exposure also potentiate glutamate levels in the dorsal striatum (Ryu et al, 2017 ). These findings suggest hyperactivation of the cholinergic system in mesolimbic and nigrostriatal projection neurons after nicotine exposure triggers the upregulation of glutamatergic neurotransmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation